Vakuumski baloni - Južnič, Stanislav (Vakuumist, 2002)
We described the vacuum balloons that were developed in the 17th and 18th centuries parallel with the hot air and hydrogen balloons. We find the technological problems that postponed their effective use in the first place. At the bicentenary of Vega's death we discussed his opinion about the vacuum ballonns. We discussed some difficulties of their modern development.
Keywords: Vega, Jurij, 1754-1802; vakuumski baloni; zgodovinski pregledi